Evaluating the impact of development projects on poverty - a handbook for practitioners (Washington DC World Bank, 2000)
Despite the billions of dollars spent on development assistance each year, there is still very little known about the actual impact of projects on the poor. There is broad evidence on the benefits of economic growth, investments in human capital, and the provision of safety nets for the poor. But for a specific program or project in a given country, is the intervention producing the intended benefits and what was the overall impact on the population? Could the program or project be better designed to achieve the intended outcomes? Are resources being spent efficiently? These are the types of questions that can only be answered through an impact evaluation, an approach which measures the outcomes of a program intervention in isolation of other possible factors.This handbook seeks to provide project managers and policy analysts with the tools needed for evaluating project impact. It is aimed at readers with a general knowledge of statistics. For some of the more in-depth statistical methods discussed, the reader is referred to the technical literature on the topic. Chapter 1 presents an overview of concepts and methods. Chapter 2 discusses key steps and related issues to consider in implementation. Chapter 3 illustrates various analytical techniques through a case study. Chapter 4 includes a discussion of lessons learned from a rich set of 'good practice' evaluations of poverty projects which have been reviewed for this handbook.
Includes bibliographical references (p. 83-93).
Keywords: Economic development projects--Evaluation--Handbooks, manuals, etc